Readability and comprehension of business organisations' occupational health and safety documents and national model codes - Taylor, Geoffrey (CCH Australia Limited, 2012)
Some aspects of readability and comprehension are reviewed following previous work on readability of occupational health and safety (OHS) documents. The results of readabiltiy assessments on OHS procedures from a range of business organisations and from draft Safe Work Australia (SWA) codes or practice are given. Readabiltiy grades on some recent mass media articles are provided as a contemporary benchmark. The results are also compared with some contemporary assessments of Australian literacy levels. The mean readabiltiy grade for business organisation documents was 14 (range 8-19), for SWA documents it was 15, while that for the media articles was 13 (range 8-16). Table 1 gives a full key to grade levels.